Lithuanian-Russian relations in 1990-1996: A study of Lithuanian foreign policy - Vitkus, Gediminas (Politologija, 1997)
This study in general is devoted to the relations between Lithuania and Russia. Despite the fact that today relations with Russia are not a top-priority issue on Lithuania’s foreign policy agenda, Russia nevertheless overshadowed the foreign policy debate by the scores of problems it provoked. On the other hand, this study goes beyond the pure subject of relation between Lithuania and Russia. It also focuses upon reasons for the concrete political decisions and raises several hypotheses on the mechanism of formation and functioning of Lithuanian foreign policy. The study is concluded by some observations on relations between large and small states, about the real possibilities of a small state pursuing its interests in its relations with a much bigger and stronger neighbor. In this respect, Lithuania’s experience is interesting in that from 1990 to 1996 it ’tested’ two types of tactics in relations with Russia. In 1990-1992, while the Sąjūdis government was in power and the formation of foreign policy was concentrated in the hands of the Chairman of the Supreme Council, Landsbergis, in Lithuania’s policy towards the Soviet Union and later towards Russia dominated a strict and uncompromising position. In contrast, after general elections in October 1992, the Lithuanian Democratic Labor Party, which received an absolute majority in the parliament, and its leader Brazauskas, who won presidential elections in February 1993, started to pursue a more adaptive policy and was trying to avoid political statements and declarations that were of no concrete use and were merely offensive in respect to Russia. The analysis of the Lithuanian-Russian relations in 1990-1996 shows that in both cases, Russia did not become more compliant or more inclined towards Lithuanian interests. Therefore, the success of Lithuanian policies towards Russia in both cases was based not on the persistency of Lithuanian politicians to promote "their own" tactics, but on their ability to find the right "mixture," i.e., a certain combination of both tactics. This publication is a revised and updated version of the following publication:Vitkus G. Lithuanian-Russian Relations in 1990-1995: A Study of Lithuanian Foreign Policy. - Forschungsschwerpunkt Konflikt- und Kooperationsstrukturen in Osteuropa an der Universität Mannheim. - Untersuchungen des FKKS 12/1996. - 46 p.